Nilai Dakwah dalam Tradisi Adodoro (Membuat Dodol) di Desa Lantang, Kecamatan Polongbangkeng Selatan, Kabupaten Takalar - Herman Jamaluddin; Rina R; Nur Aisyah (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2022)
The formulation of the problem studied in this study is How are Da'wah Activities in the A'dodoro Tradition in Lantang Village, South Polongbangkeng District, Takalar Regency? and What is the Value of Da'wah in the A'dodoro Tradition in Lantang Village, South Polongbangkeng District, Takalar Regency? The purpose of this study was to describe the activity of making dodol in Lantang Village, South Bontonmpo District, Takalar Regency and to find the value of da'wah in the tradition of making dodol in Lantang Village, South Polongbangkeng District, Takalar Regency. This study uses a descriptive qualitative research method where this type of research only tries to describe and analyze the A'dodoro Tradition as a Da'wah Activity in the Lantang area. The data were dug in depth with interview, observation and documentation techniques. The results of this study indicate that the value of da'wah contained in the a'dodoro tradition is the value of community solidarity, the value of generosity and the value of gratitude.